Model Hubungan Pola Pemberdayaan dan Pengembangan Kepribadian dengan Dinamika Kelompok Tani Lada di Kawasan Perbatasan Kalimantan Barat: Relationship Model of Empowerment Patterns and Personality Development with Group Dynamics of Pepper Farmers in the Border Area of West Kalimantan - Komariyati, Komariyati; Kurniady, Dedy; Nugraha, Aditya (Journal of Integrated Agribusiness, 2024)
The study aims to investigate and analyze the relationship between empowerment patterns and personality development with group dynamics. Conducted in Entikong District, a border area in West Kalimantan, the study utilized primary data from 100 respondents selected through simple random sampling. Data collection involved questionnaires and documentation, with data analysis performed using SEM through SmartPLS. The study’s findings include: (1) Personality development significantly affects group dynamics, with a coefficient of 0.355, t-statistic of 4.613 <1.96, and p-value of 0.000 <0.05; (2) Empowerment patterns significantly affect group dynamics, with a coefficient of 0.382, t-statistic of 4.096> 1.96, and p-value of 0.000 <0.05; (3) Empowerment patterns have no significant effect on personality development, with a coefficient of 0.140, t-statistic of 1.221 < 1.96, and p-value of 0.223 > 0.05; and (4) Personality development does not mediate the effect of empowerment patterns on group dynamics, indicated by a coefficient of 0.050, t-statistic of 1.149 < 1.96, and p-value of 0.251 > 0.05.